PYTHON-POWERED DATA ANALYSIS THROUGH WEB SCRAPING - Ravikiran, Sanga; Kavitha, Valasa; Ismail, Mohammad; Ramalakshmi, Pallinti (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
The rationality approach to developing extrapolation exams, for example, and small-scale, subjective, and quantitative examinations are all forms of standard information investigations that are founded on the root-and-effect relationship. The contrast between the Web Scraper's cunning ethics and techniques explains how the scraper operates. The three steps of the process are as follows: first, the web scraper gathers the necessary connections from the internet; second, the data is extracted from the source links; and third, the data is saved in a CSV file. The task is performed using the Python programming language. By doing this, along with the moral library knowledge and practical know-how, we might be able to obtain the necessary Scraper in our possession. Python's extensive community, library resources, and elegant coding style make it the ideal language for extracting required data from the target website.